2011
DOI: 10.5551/jat.10470
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Serum Apolipoprotein B-48 Can be a Marker of Postprandial Hyperlipidemia

Abstract: Aim: Postprandial hyperlipidemia (PH) is thought to be caused by the impaired postprandial metabolism of triglycerides (TG)-rich lipoproteins in both endogenous and exogenous pathways; however, there is no consensus. It is difficult to estimate the presence of PH without performing a time-consuming oral fat loading (OFL) test, so postprandial lipoprotein metabolism was analyzed by measuring the postprandial levels of apolipoprotein (apo) B-48 and apo B-100, and the correlation between postprandial TG increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
1
41
1
Order By: Relevance
“…In AB subjects, the fasting serum concentration of apoB was associated with fasting small LDL particle concentration. Although our study described the relationship between fasting apoB concentrations and PPL responses, Masuda et al 26 reported that after an oral fat load, fasting apoB-48 concentrations correlated with TG AUC after a high-fat meal; a correlation was also observed for fasting and stimulated levels of apoB-48. These findings suggest that a high-fat meal results in higher postprandial TG concentrations because of elevated apoB-48 remnant production from the small intestine, with little increase in serum LDL-c hepatic production of apolipoprotein B100.…”
contrasting
confidence: 50%
“…In AB subjects, the fasting serum concentration of apoB was associated with fasting small LDL particle concentration. Although our study described the relationship between fasting apoB concentrations and PPL responses, Masuda et al 26 reported that after an oral fat load, fasting apoB-48 concentrations correlated with TG AUC after a high-fat meal; a correlation was also observed for fasting and stimulated levels of apoB-48. These findings suggest that a high-fat meal results in higher postprandial TG concentrations because of elevated apoB-48 remnant production from the small intestine, with little increase in serum LDL-c hepatic production of apolipoprotein B100.…”
contrasting
confidence: 50%
“…Fasting apo B-48 levels are correlated with postprandial TG increase 19) and are significantly higher in patients with accumulated CM and CM remnants 17) and metabolic syndrome (MetS) 20) . High fasting apo B-48 levels are correlated with premature carotid artery stenosis 21,22) , and postprandial increases in TG and apo B-48 are correlated with CHD 23) .…”
Section: Subjects and Patientsmentioning
confidence: 99%
“…For many years, CM and CM remnants were believed the major source of lipoproteins in postprandial hyperlipidemia. ApoB-48 containing particles of CM origin increased in parallel with plasma TG after food ingestion [17,36,88,114]. This finding led to the assumption that the major remnant component was composed of CM remnants.…”
Section: Fractionation and Analysis Of Apob-48 In Rlp By Gel Exclusiomentioning
confidence: 86%
“…3.5). These results suggested that CM or CM remnants are the major component of increased postprandial remnant lipoproteins [88]. However, plasma apoB-100 was far greater than apoB-48.…”
Section: Daily Rhythm Of Plasma Tg Apob-48 and Remnant Lipoproteinsmentioning
confidence: 93%